Host-specific differences in the contribution of an ESBL IncI1 plasmid to intestinal colonization by Escherichia coli O104:H4. (28th February 2018) - Giles, M; Cawthraw, S A; AbuOun, M; Thomas, C M; Munera, D; Waldor, M K; La Ragione, R M; Ritchie, J M
Abstract: Objectives: To assess stability and contribution of a large ESBL-encoding IncI1 plasmid to intestinal colonization by Escherichia coli O104:H4 in two different mammalian hosts. Methods: Specific-pathogen-free 3–4-day-old New Zealand White rabbits and conventionally reared 6-week-old weaned lambs were orally infected with WT E. coli O104:H4 or the ESBL-plasmid-cured derivative, and the recovery of bacteria in intestinal homogenates and faeces monitored over time. Results: Carriage of the ESBL plasmid had differing impacts on E. coli O104:H4 colonization of the two experimental hosts. The plasmid-cured strain was recovered at significantly higher levels than WT during late-stage colonization of rabbits, but at lower levels than WT in sheep. Regardless of the animal host, the ESBL plasmid was stably maintained in virtually all in vivo passaged bacteria that were examined. Conclusions: These findings suggest that carriage of ESBL plasmids has distinct effects on the host bacterium depending upon the animal species it encounters and demonstrates that, as for E. coli O157:H7, ruminants could represent a potential transmission reservoir.